Diagnostic and prognostic challenges in Idiopathic Pulmonary Fibrosis: A patient's "Q and A" approach. (February 2017) - Tzouvelekis, Argyris; Tzilas, Vasilios; Papiris, Spyridon; Aidinis, Vassilis; Bouros, Demosthenes
Abstract: Idiopathic Pulmonary Fibrosis (IPF) is a chronic, progressive, debilitating disease of unknown etiology that leads to death nearly half of the patients within 3–3.5 years. The past 15 years, the scientific community has made tremendous progress towards standardized diagnostic and prognostic algorithms that led to the generation of the 2011 ATS/ERS/JRS/ALAT guidelines. The latest guidelines provided us with fundamental diagnostic algorithms that set the diagnosis in the majority of cases; however, they leave a significant minority of patients without diagnostic and most importantly, therapeutic umbrella. To this end current guidelines should be revisited in light of research advances, including the tools of "fibromics" and at the same time provide practical guidance to the real-world of IPF in order to address patients' needs. The scope of this review article is to summarize challenges in the everyday IPF clinical practice and make an effort to provide realistic answers to patients' questions.